Churchill and the United States of Europe, 1904-1948 (Comillas Journal of International Relations, 2016)
The call for a “United States of Europe” is a recurring theme in the writings and speeches of Sir Winston Churchill from at least 1930, and reaches its culmination in his opening address to the Congress of Europe held at The Hague in May 1948. This article analyses Churchill’s own writings and oratory to trace the origins of his support for closer European union. Initially he envisaged Britain as a guarantor and facilitator of European unity, but by 1948 he had become an advocate of a role for Britain within Europe. This shift in thinking is followed through analysis of his language and explained in terms of the historical context.